On a Sobolev Type Theorem for the Generalized Riesz Potential Generated by the Generalized Shift Operator on Morrey Space - Sarikaya, Mehmet Zeki; Yildirim, Hüseyin (Sarajevo Journal of Mathematics, 2024)
In this paper, we give a generalized definition of Morrey space for Lebesgue measure. In this space, the inequality of Hardy-Sobolev type is established for the generalized Riesz potentials generated by the generalized shift operator. 2000 Mathematics Subject Classification. 31B10, 44A15